Seismic and Geodetic Evidences of a Hydrothermal Source in the Md 4.0, 2017, Ischia Earthquake (Italy). Issue 5 (31st May 2019) - Calderoni, Giovanna; Di Giovambattista, Rita; Pezzo, Giuseppe; Albano, Matteo; Atzori, Simone; Tolomei, Cristiano; Ventura, Guido
Abstract: Seismic events characterize active hydrothermal and volcanic areas and may be due to magma/fluid migration, hydrothermal pressurization, gravitational instability, and local tectonics. On 21 August 2017, an Md 4.0 earthquake occurred at Ischia volcanic island (Italy), within an active hydrothermal system. We analyze seismic, Global Positioning System, and interferometric synthetic aperture radar data to shed light on the source mechanism of such an event. The low‐frequency content (2 Hz), the low stress drop (0.01 MPa), and a low S/P spectral ratio suggest the involvement of fluids in the source mechanism. The focal mechanism suggests a mixed shear‐tensile (opening) rupture with the P first arrivals showing up movements in the nearest stations. Geodetic data describe an E‐W elongated area of coseismic subsidence overlapping a WSW‐ENE fault bounding the hydrothermal reservoir at depth. The modeled deformation field is consistent with a two‐source model consisting of a WSW‐ESE striking, north dipping normal fault, and a closing subhorizontal crack. This closure immediately followed an initial opening related to a fluid pressurization event responsible for the earthquake. We show that moderate magnitude earthquakes in active hydrothermal areas may be associated with the pressurization/depressurization cycles of a hydrothermal reservoir due to self‐sealing processes and not to the arrival of new fluids from depth. Other events like that recorded at Ischia, which have affected the island in historical times, are not necessarily associated with 'volcanic unrest' episodes and imply the occurrence of fault‐valve mechanisms. Therefore, the dynamics of hydrothermal systems must be taken into account in the seismic hazard evaluation. Key Points: The Md =4.0, 2017 damaging event at Ischia volcanic island is characterized by low‐stress drop and S/P ratio The source includes shear faulting and cracks opening followed by closure (subsidence) Hydrothermal, nonmagmatic earthquakes must be considered in the evaluation of volcanic hazard at active volcanoes